Metodologia segmentacji rynku ubezpieczeniowego - Mojsiewicz, Magdalena; Wawrzyniak, Katarzyna (Methodology of Insurance Market Segmentation, 2005)
In the article was presented classification of market segmentation, beginning from the social-demographic, preferences to behavior segmentation. For the sample of polish households in which was observed the loyalty to mark, risk perception, independence by buying insurance and price, 4 classes of clients was distinguished. Most of case was in the first class, so called non-rational clients. For this group was proposed segmentation by inclinations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 416-422